Unveiling the Pathways: Mapping and Understanding Hidden Homelessness Among 2SLGBTQ+ Youth in Ontario - Katie MacEntee; Nicole Elkington; John Segui; Alex Abramovich (Youth)
Transphobic and homophobic violence and discrimination within homes and housing programs lead many 2-Spirit, lesbian, gay, bisexual, transgender, and queer (2SLGBTQ+) youth to find alternative, temporary, and insecure housing. These types of living situations are considered “hidden homelessness”. This study interviewed 2SLGBTQ+ youth (n = 6) and key informants (n = 12) who have experienced and/or who support hidden homelessness across three sites in Ontario (Toronto, York Region, and London). The results suggest experiences of hidden homelessness for 2SLGBTQ+ youth are nonlinear, with pathways driven by family conflict combined with the high cost of living and lack of employment, making independent living unaffordable. Additionally, youth avoid services where they experience discrimination and often experience social isolation. In rural and suburban areas, youth have fewer options for safe and inclusive services. When services are accessible, wrap-around supports that address the complexity of their situations help youth exit hidden homelessness. Prevention strategies should focus on addressing family conflict and supporting reunification when it is safe to do so. For those who are unable to return home, there is a need for increased financial support and more affordable housing. Building comprehensive population-based support services is recommended to address the overrepresentation of 2SLGBTQ+ youth experiencing homelessness.